2014
DOI: 10.15829/1560-4071-2014-6-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Risk Factors for Cardiovascular Death: Data From 12-Year Prospective Epidemiologic Study

Abstract: Цель. Изучение влияния социально-экономических факторов на относитель-ный риск (ОР) смерти от сердечно-сосудистых заболеваний (ССЗ) в неоргани-зованной популяции города Тюмени. Материал и методы. Эпидемиологическое исследование было проведено стандартными методами на репрезентативной выборке жителей г. Тюмени 25-64 лет. В течение последующих 12 лет вся обследованная тюменская когорта (795 мужчин и 813 женщин) была подвергнута анализу смертей от сер-дечно-сосудистых заболеваний (ССЗ). Мультивариантная регрессио… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Also, Floud et al suggested the possibility that healthy women may be less likely to divorce,13 although Akimova et al reported that divorced and single women were more highly educated and had a higher qualified occupation which results in greater financial independence and better quality of life 35…”
Section: Discussionmentioning
confidence: 99%
“…Also, Floud et al suggested the possibility that healthy women may be less likely to divorce,13 although Akimova et al reported that divorced and single women were more highly educated and had a higher qualified occupation which results in greater financial independence and better quality of life 35…”
Section: Discussionmentioning
confidence: 99%
“…For example, research by Nandi et al (2014) and Stringhini et al (2010) shows that risks of people with low and high social status but do not have these habits are different. Akimova et al (2014) conducted a 12-year study in the Tyumen region of the Russian Federation and found that 10.7% of men's deaths and 4.1% of women are caused by CVD. Men with lower levels of education are more likely to have CVD.…”
Section: Discussionmentioning
confidence: 99%
“… 50 It is further highlighted that married status can exert a buffering role through the informational or emotional resources from a spouse promoting adaptive behavior and reducing the excessive neuroendocrine response to acute or chronic stressors translated to a reduced risk of cardiovascular diseases. 51 …”
Section: Discussionmentioning
confidence: 99%